Sustainable production of oxalic acid from waste cane sugar molasses via systemic recycling of nitrogen oxide. (10th March 2022) - Mottakin, M.; Selvanathan, Vidhya; Mandol, Sajal; Mosaddek Hossen, Md.; Nurunnabi, M.; Haider, Jahid Bin; Hasan, Mahfujul; Althubeiti, Khaled; Sarkar, D.K.; Shahinuzzaman, M.; Abdullah, Huda; Akhtaruzzaman, Md.
Abstract: An effective and environmentally benign method of producing oxalic acid from nitric acid oxidation of waste cane sugar was conducted via a sequence of reactors. Nitrogen oxides (NOx ) formed within the first batch of reactor were reused in the subsequent reactor to prevent the wastage of oxidizer. In addition, the excess nitrogen oxides from the second reactor were channeled into a last reactor comprising of ammonia (NH3 ) solution to consume the remaining NOx gas into ammonium nitrate (NH4 NOx ), to be used as fertilizer. Inclusion of vanadium pentoxide (V2 O5 ) as the catalyst improved the yield from 34.8% to 55.6% in the first reactor. This value was further improved to 57.8% upon incorporation of titanium dioxide (TiO2 ) as catalyst promoter with V2 O5 at 2:10 M ratio. In addition, various reaction parameters such as air flow rate, time, temperature, feed concentration and solvent to feed ratio were optimized to produce a maximum yield of 60.2%. To investigate the possibility of maximum number of reactors that can be catered by the initial nitrogen oxide composition, the batch of reactors were extended up to four. Maximum yield of 60.2% was obtained for the first stage, and 55.3%, 39.5%, 18.7% were obtained for the 2nd, 3rd, and 4th stages respectively. Kinetic analysis was performed to determine the reaction order and activation energy. Highlights: Sustainable production of oxalic acid from waste cane sugar. Systemic recycling of nitrogen oxide gases was adopted to maximize yield. Novel combination of TiO2 -V2 O5 based catalyst improved oxalic acid yield. Proposed approach enhances product yield and process sustainability.